THE EMPLOYMENT AND WAGE SPILLOVER EFFECTS OF SLOVENIA‟S 2010 MINIMUM WAGE INCREASE - Matija Vodopivec (European Scientific Journal, ESJ, 2015)
We analyse the effects of a large increase in Slovenia‘s minimum wage in March 2010 using administrative data covering the entire population of labour force participants. We find that the minimum wage increase had a significant and sizable negative effect on the job retention of minimum wage recipients, especially of young and low-education workers, and also led to an increased probability of job-to-job transitions for minimum wage recipients. In addition, we find evidence of spillover effects of the minimum wage increase on wages higher in the wage distribution, with the effects monotonically decreasing with wages but still present at 150 percent of the new minimum wage. The results are based on a difference-in-differences approach in which the treatment group is comprised of workers whose wages at the time of the introduction of the minimum wage raise were below the new minimum wage, and the control group is comprised of workers whose wages were slightly above the new minimum wage.